Stigma in the health clinic and implications for PrEP access and use by adolescent girls and young women: conflicting perspectives in South Africa - Laura Nyblade; Jacqueline W. Ndirangu; Ilene S. Speizer; Felicia A. Browne; Courtney Peasant Bonner; Alexandra Minnis; Tracy L. Kline; Khatija Ahmed; Brittni N. Howard; Erin N. Cox; Abigail Rinderle; Wendee M. Wechsberg (BMC Public Health, 2022)
Abstract Background Globally, an urgent need exists to expand access to HIV prevention among adolescent girls and young women (AGYW), but the need is particularly acute in sub-Saharan Africa. Oral pre-exposure prophylaxis (PrEP) offers an effective HIV prevention method. In many countries, however, accessing PrEP necessitates that AGYW visit their local health clinic, where they may face access challenges. Some countries have implemented youth-friendly services to reduce certain challenges in local health clinics, but barriers to access persist, including clinic stigma. However, evidence of clinic stigma toward AGYW, particularly with respect to PrEP service delivery, is still limited. This mixed methods study explores stigma toward AGYW seeking clinic services, in particular PrEP, from the perspective of both clinic staff (clinical and nonclinical) and AGYW who seek services at clinic sites in Tshwane province, South Africa. Methods Six focus group discussions were conducted with AGYW (43 total participants) and four with clinic staff (42 total participants) and triangulated with survey data with AGYW (n = 449) and clinic staff (n = 130). Thematic analysis was applied to the qualitative data and descriptive statistics were conducted with the survey data. Results Four common themes emerged across the qualitative and quantitative data and with both AGYW and clinic staff, although with varying degrees of resonance between these two groups. These themes included (1) clinic manifestations of stigma toward AGYW, (2) concerns about providing PrEP services for AGYW, (3) healthcare providers’ identity as mothers, and (4) privacy and breaches of confidentiality. An additional theme identified mainly in the AGYW data pertained to stigma and access to healthcare. Conclusion Evidence is needed to inform strategies for addressing clinic stigma toward AGYW, with the goal of removing barriers to PrEP services for this group. While awareness has increased and progress has been achieved around the provision of comprehensive, youth-friendly sexual and reproductive health services, these programs need to be adapted for the specific concerns of young people seeking PrEP services. Our findings point to the four key areas noted above where programs seeking to address stigma toward AGYW in clinics can tailor their programming.